2018
DOI: 10.3390/horticulturae4030026
|View full text |Cite
|
Sign up to set email alerts
|

Pecan Propagation: Seed Mass as a Reliable Tool for Seed Selection

Abstract: Pecan is one of the most important horticultural nut crops in the world. It is a deciduous species native to the temperate zones of North America, introduced into the subtropical regions of Brazil during the 1870s. High quality seedlings are essential to establishing healthy and productive orchards, and selection of seeds is an important factor in this issue. In this study we evaluated the correlation between seed mass, emergence rate and morphometric traits of seedlings in the pecan cultivar Importada. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The fourth contribution was "Pecan Propagation: Seed Mass as a Reliable Tool for Seed Selection" by Poletto et al [32]. High-quality seedlings are essential in establishing healthy and productive orchards, and studies on new technologies for pecan (Carya illinoinensis (Wangenh) K. Koch) cultivation in subtropical regions have mostly focused on seedling production [33,34].…”
Section: Fruit Cropsmentioning
confidence: 99%
“…The fourth contribution was "Pecan Propagation: Seed Mass as a Reliable Tool for Seed Selection" by Poletto et al [32]. High-quality seedlings are essential in establishing healthy and productive orchards, and studies on new technologies for pecan (Carya illinoinensis (Wangenh) K. Koch) cultivation in subtropical regions have mostly focused on seedling production [33,34].…”
Section: Fruit Cropsmentioning
confidence: 99%
“…Several species of tribe Juglandeae -as Juglans regia (walnut), Cyclocarya palliurus (wheel wingnut), Carya sinensis (Chinese hickory) and Carya illinoinensis (hickory or pecan) -are important crop tree species cultivated in several regions of the world aiming at the commercial production of nuts. Pecan is one of the most important nut crop species in the world, cultivated in several countries in North America (USA and Mexico), South America (Peru, Argentina, and Brazil), Africa (South Africa and Egypt), Asia (Israel and China) and Australia (Poletto et al 2018). The species was introduced in Brazil with commercial interest during the 1870s and farmers needed to select cultivars adapted to the climatic and biological conditions where the orchards were established (Poletto et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, seed weight was highly correlated with the germination and emergence dimensions for all three evaluated citrus rootstocks. Previous studies have showed strong relationship between seed weight and seedling growth measurements, including germination and emergence, among different species (Hanley et al, 2007;Huang et al, 2017;Poletto et al, 2018). The control of seed mass and size are regulated by genetic and epigenetic pathways, but it has been little investigated in woody perennial plants (Poletto et al, 2018).…”
Section: Source Of Variancementioning
confidence: 99%
“…Previous studies have showed strong relationship between seed weight and seedling growth measurements, including germination and emergence, among different species (Hanley et al, 2007;Huang et al, 2017;Poletto et al, 2018). The control of seed mass and size are regulated by genetic and epigenetic pathways, but it has been little investigated in woody perennial plants (Poletto et al, 2018). Current evidence has shown that the homolog of Auxin Response Factor 19 (JcARF19) significantly increases seed size and mass in Jatropha curcas plants, confirming the importance of the auxin pathway in controlling these seed attributes in woody perennial plants (Sun et al, 2017).…”
Section: Source Of Variancementioning
confidence: 99%
See 1 more Smart Citation